Trade Liberalization, Macroeconomic Adjustment, and Welfare : Unifying Trade and Macro Models - Choudhri, Ehsan (IMF Working Papers; Working Paper ;, 2006)
Trade liberalization leads to long-run gains, but it can also involve costly short-run macroeconomic adjustment. The paper explores the relative importance of these effects within a dynamic general equilibrium model that captures key elements of both international trade and macroeconomic models. The welfare effect of trade liberalization is decomposed into a steady-state efficiency gain and a transitional loss associated with wage-price stickiness. Our estimates show that the transitional loss is small relative to the steady-state gain, and tends to be lower under flexible as compared to fixed exchange rates. We also show that the loss can be reduced further by a flexible price-level targeting policy rule.